Eccentric-concentric ratio: A key factor for defining strength training in soccer - Nunez, F. J.; Hoyo, M. de; Lopez, A. Muñoz; Sanudo, B.; Otero-Esquina, C.; Sanchez, H.; Gonzalo-Skok, O. (International Journal of Sports Medicine, 2019)
The aims of this study were to analyse the effect of chronic strength training over concentric power (CON), eccentric power (ECC), ECC/CON ratio, and 20?m linear sprint performance in elite young soccer players. Twenty young elite Spanish soccer players were assigned to an experimental group (CPG) which performed a front-step exercise using a conical pulley, 2-3 sets of 6 repetitions each leg, during 9 weeks (CPG, n=10) in addition to its usual strength training, or to a control group (CG, n=10). The improvements in the ECC mean power (36%, ES=1.61), and ECC / CON ratio (17%, ES=1.77) were substantially greater in the CPG than in the CG while the CON mean power (16%, ES=0.83) was substantially greater in the CG than in the CPG. The sprinting time for 10?m (2.8%, ES=0.78) and the 10?m flying time between 10-20?m (1.72%, ES=0.41) were substantially enhanced in CPG and CG respectively. To be efficient when defining a functional strength training and performance increments using an inertial device, the mean power output need to be measured during the CON and ECC phases and an analysis of the ECC / CON ratio should be included.